Georgia Architectural and Historic Properties Survey of Morven [018] Main St. Hahira West, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Morven [018] Main St. Hahira West, Ga. December 1980. Church of irregular plan. High gabled roof. Square posts at shed porch. Shiplap siding. Double hung sash windows with 4/4 lights. Brick piers filled in. Good condition. Date of Construction: c. 1907. Not significant as part of a potential National Register historic district. Area not extensive enough historically.
Georgia Architectural and Historic Properties Survey of Morven [018] Main St. Hahira West, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.03 MB (1,089,908 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Morven, Ga.; Hahira (Ga.)